Deletion of Rap1 disrupts redox balance and impairs endothelium-dependent relaxations. (February 2018) - Wong, Kenneth H.K.; Cai, Yin; Ying, Fan; Chen, Xinyi; Vanhoutte, Paul M.; Tang, Eva H.C.
Abstract: Aims: Repressor activator protein 1 (Rap1) is conventionally known as a static structural component of the telomere, but recent evidence indicates that it exerts functions within and outside the nucleus taking part in metabolic regulation and promoting inflammatory responses. The present study investigated whether or not Rap1 deletion affects oxidative stress and nitric oxide (NO) bioavailability in the vascular wall, thus modulating endothelial function. Methods and results: Vascular responsiveness was studied in wire myographs in aortae from Rap1 wildtype and knockout mice. Deletion of Rap1 impaired endothelium-dependent relaxations elicited by acetylcholine. Rap1 deficiency did not affect the activation of endothelial NO synthase or the sensitivity of vascular smooth muscle to NO donors. The blunted acetylcholine-mediated relaxations in Rap1 deficient aortae were restored with nicotinamide adenine dinucleotide phosphate (NADPH) oxidase inhibitors, apocynin or VAS2870. Rap1 deletion lowered cellular thiol-redox status and diminished activities of thiol-redox enzymes, thioredoxin 1 and glutaredoxin 1. Conclusions: The capacity of thioredoxin 1 and glutaredoxin 1 to reduce intra-protein disulfide bridges is weakened in Rap1 deficient mice, resulting in hyper-activation of NADPH oxidase and greater reactive oxygen species generation. The high oxidative stress in Rap1 deficient mice is implicated with greater oxidative breakdown of NO, explaining the blunted acetylcholine-mediated relaxations in this animal. These findings imply that Rap1 plays an unanticipated role in regulating the fate of NO (a pivotal determinant of vascular homeostasis) and thus identify a new physiological importance of the telomere-associated protein. Highlights: Reduced NO bioavailability in Rap1 -/- mice is caused by greater NO destruction by ROS derived from NADPH oxidase. Weakened capacity of Trx1 and Grx1 to reduce intra-protein disulfide bridges in Rap1 -/- mice augments ROS generation. Rap1 protein is a novel gatekeeper against oxidative breakdown of NO. Deletion of Rap1 is associated with premature ROS-mediated endothelial dysfunction.